PARENTAL SUPPORT AND STUDENT DISCIPLINE IN LEARNING: INSIGHTS FROM A QUANTITATIVE CORRELATIONAL STUDY - Rahmatul Fauzana; Triyono; Besti Nora Dwi Putri (EDUCATIONE, 2026)
This study examines the problem of suboptimal learning discipline among students—manifested in behaviors such as tardiness, incomplete assignments, and inconsistent study routines—and investigates whether parental social support is associated with stronger learning discipline. The study aimed to (1) describe parental social support, (2) describe students’ learning discipline, and (3) test the relationship between the two variables among Grade XI students at MAN 1 Pasaman Barat. A quantitative correlational design was used with a sample of 65 students drawn from a population of 230. Data were collected using Likert-type questionnaires (31 items measuring parental social support and 35 items measuring learning discipline) and analyzed using Pearson’s product–moment correlation. The results indicated that parental social support was generally high (58.85% in the high category), while learning discipline was moderately high (63.08% in the moderately high category). Correlation analysis revealed a significant positive relationship between parental social support and learning discipline (r = 0.499; p < .001). In conclusion, stronger parental support is associated with better student learning discipline. The findings imply that schools should strengthen parent–school collaboration and guidance and counseling initiatives to foster disciplined study habits. Future studies should employ broader and more diverse samples, longitudinal designs, and multivariate models to test potential mechanisms (e.g., motivation and self-regulation) and improve causal interpretation.